Step
*
1
of Lemma
rmul-inverse-is-rinv
1. x : ℝ
2. x ≠ r0
3. t : ℝ
4. (x * t) = r1
5. (rinv(x) * r1) = rinv(x)
⊢ t = rinv(x)
BY
{ ((RWW "-2<" (-1) THEN Auto) THEN RWW "rmul-assoc rmul-rinv2" (-1) THEN Auto THEN nRNorm (-1) THEN Auto)⋅ }
Latex:
Latex:
1.  x  :  \mBbbR{}
2.  x  \mneq{}  r0
3.  t  :  \mBbbR{}
4.  (x  *  t)  =  r1
5.  (rinv(x)  *  r1)  =  rinv(x)
\mvdash{}  t  =  rinv(x)
By
Latex:
((RWW  "-2<"  (-1)  THEN  Auto)
  THEN  RWW  "rmul-assoc  rmul-rinv2"  (-1)
  THEN  Auto
  THEN  nRNorm  (-1)
  THEN  Auto)\mcdot{}
Home
Index